IMPROVING STUDENT LEARNING OUTCOMES OF GRADE V BY USING THE THINK PAIR SHARE COOPERATIVE LEARNING MODEL IN THEMATIC LEARNING AT SDN SUNGAI SALAI HILIR - Adrian, Yudha (Journal of Elementary Education, 2024)
This study aims to determine the effectiveness of the Think Pair Share cooperative learning model in improving student learning outcomes in thematic learning, especially theme 8 subtheme 3. This classroom action research was conducted at SDN Sungai Hilir involving 26 grade V students and homeroom teachers. The results showed a significant increase in student learning outcomes after the implementation of the Think Pair Share model. Student involvement in the learning process also increased, as evidenced by the increase from cycle I to cycle II. Teachers also showed an increase in managing learning by implementing the Think Pair Share cooperative model, as seen from the changes in cycle I and cycle II.